Gestión de logística y su impacto en la operatividad de los inventarios de la empresa feilo sylvania n.v. del cantón guayaquil año 2024. - Tuarez Anchundia, Janeth Katherine (2025)
This research project focused on evaluating the logistics management of FEILO SYLVANIA N.V. during the year 2024, with the objective of identifying the main operational limitations that affected process efficiency and real inventory availability. The introduction contextualized the problem related to bottlenecks in supply, manual inspection of products, and the lack of synchronization in the digital registration of goods. A mixed-method approach was applied, involving structured interviews, document analysis, process flow diagrams, and statistical evaluation of unloading times, complemented by the application of a tool for detecting logistics waste (muda). The results revealed non-value-adding activities such as overprocessing, waiting times, and unnecessary inventory, as well as statistical outliers and operational incidents affecting inventory performance. Based on the diagnosis, optimization strategies were proposed in three areas: internal processes, coordination with delivery providers, and commercial actions to improve product turnover. The recommendations focus on implementing sampling audits, early document validation, delivery traceability, and coordinated efforts between logistics, IT, and commercial departments to enhance efficiency, reduce errors, and strengthen customer service.